A Simple Secretion Assay for Assessing New and Existing Myocilin Variants. (3rd June 2022) - Nakahara, Emi; Hulleman, John D.
Abstract: Purpose: A lack of sufficient functional information exists for appropriately categorizing a large number of myocilin (MYOC) variants and their involvement in primary open angle glaucoma, hindering their clinical significance classification. Most glaucoma-causing MYOC mutations result in protein non-secretion and intracellular insoluble aggregate formation in cultured cells. Herein, we generated a Gaussia luciferase-based MYOC fusion protein to quickly and sensitively track the secretion of MYOC variants and compared these results to the better-established western blotting assay for MYOC. Methods: Fourteen clinically-derived MYOC variants with varying degrees of predicted pathogenicity were transfected into HEK-293A cells and analyzed by either a luciferase assay or western blotting. Results: Eight of the variants (G12R, V53A, T204T, P254L, T325T, D380H, D395_E396insDP, and P481S) had not been biochemically assessed previously. Of these, P254L and D395_E396insDP demonstrated significant secretion defects reminiscent of glaucoma-causing mutations. The luciferase assay results agreed with western blotting for thirteen of the fourteen variants (93%), suggesting a strong concordance. Conclusions: These results suggest that the Gaussia luciferase assay may be used as a complementary or standalone assay for quickly assessing MYOC variant behavior and we anticipate that these results will be useful in MYOC variant curation and reclassification.